MINAT BACA SISWA DITINJAU DARI DUKUNGAN ORANG TUA DAN MOTIVASI BERPRESTASI - Da'watul Anis Ma'rufah; Daliman; M. Agus Wahyudi (LP3M IAI Al Urwatul Wutsqo Jombang, 2021)
The aim of this study was to analyze the relationship between students' interest in reading and parents support and motivation for achievement. The collection data method used in this study was a scale method, and the population of this study was 720 high school students. Sampling of the type used is cluster random sampling to give all classes an equal chance. Sampling from 8 existing classes resulted in 5 classes with a total of 150 students. Charging scale is carried out in each class for a predetermined amount of time. From the results of the study, the calculation of the regression analysis of achievement motivation according to parental support and reading interest obtained a value of R = 0.201. p = 0.000; (p <0.05) Fcount = 18.520, sig. = 0.000 <0.05, which indicates that X1, X2 and Y are linear. These results indicate that there is an important relationship between parental support and interest in reading and motivation for achievement.